Evaluating hydrogen risk management policy PR: Lessons learned from three hydrogen accidents in South Korea - Lee, Youhyun; Cho, Min Hyuk; Lee, Min Chul; Kim, Young Jin (International Journal of Hydrogen Energy, 2023)
Hydrogen energy has become a pivotal actor in achieving carbon neutrality by 2050 in the era of the climate crisis. Regardless of its importance, three consecutive hydrogen safety accidents and their aftermath in South Korea have aggravated the public's acceptance of hydrogen. Hydrogen-induced risks have always existed in our society regardless of technical improvement. Here, the task of the government is to manage the hydrogen risk to prevent hydrogen disasters. This study included three steps in its research design; 1) selecting experts through snowball sampling, 2) conducting a qualitative email survey, and 3) analyzing the qualitative answer sheet by applying semantic network analysis. We found that experts' evaluations of the Korean hydrogen PR policy were positive regarding responsiveness but negative regarding openness, guidelines, and control tower. Therefore, we suggest practical policy recommendations; the central government should play an important role in cultivating professional crisis management PR personnel and others.
Keywords: Carbon neutralities; Hydrogen accident; Hydrogen Energy; Hydrogen risks; Hydrogen safety; Management policy; Policy PR; Risks management; Safety accidents; South Korea; Hydrogen accident; Hydrogen risk; Hydrogen safety; Policy PR; Risk management